Conceptual Study of Vedini Twacha Sharir with special reference to Visarpa Vyadhi (Herpes Zoster) (AYUSHDHARA, 2023)
Ayurveda is holistic science and traditional system of Indian medicine. It belongs to maintain the balance of Dosha, Dhatu, and Mala for wellbeing of human. In medical science, anatomy has prime importance in order to diagnose and treat the disease. As Sharirsthana are explained in Ayurveda Samhitas to understand the development of internal and external body parts. Twacha (skin) is the important part of our body which is one among the five Dnyanendriyas (sensory organ).Twacha (skin) is one of the biggest and outermost protecting organs of the body. Sapta Twacha, it’s Utpatti, its thickness, and Sapta Twacha related disease has mentioned in Sushruta Samhita. Each layer has its own significance, as it is a site of respective disease. Out of seven layers Vedini Twacha belongs to fifth layer with associated disease Kushtha and Visarpa. Sign and symptoms of Visarpa are found to be kindred with Herpes Zoster in modern medicine. Current article embellished the Vedini Twacha is a locus for Visarpa Vyadhi (herpes Zoster).